G496(P) Bronchiolitis high dependency management: the edinburgh experience. (May 2019) - Bee, N; Best, E; Stark, M
Abstract : Background: In our tertiary paediatric centre, ten percent of patients admitted with a diagnosis of bronchiolitis require high dependency (HDU) care. Our unit does not currently offer high frequency nasal cannulae oxygen (HFNCO 2 ) on the wards, but plans to initiate this. Aims: To complete a retrospective analysis of patients requiring escalation to HDU care, their management, length of stay and need for intensive care admission. Additionally, to assess the potential impact of introducing ward HFNCO2 . Methods: All admissions with bronchiolitis in infants under 14 months of age (n=509) from October 2016 to April 2017 were identified. There were 53 admissions to HDU; forty nine had complete electronic clinical records available to review. Results: Table one shows the management strategies used, with 96% of patients commencing non-invasive respiratory support. A total of 10% of patients were subsequently admitted to paediatric intensive care, with 4% requiring intubation. There was similar frequency of use of CPAP and HFNCO 2 as a first line treatment. Thirty-five percent were treated with HFNCO 2 alone. When patients deteriorated despite non-invasive ventilation, rescue treatment with the other method was used. Of these ten cases (20%), only one subsequently required paediatric intensive care. Table 1 Conclusion: Our centre currently uses HFNCO2 and CPAP in the HDU management of bronchiolitis. From this data, introducing ward HFNCO2 appears to have the potential to reduce over a third of HDU admissions. This data also supports the use of rescue treatment with the alternative mode of respiratory support to reduce admissions to our PICU.